Gacha Mechanisms and Digital Consumer Behavior: A Systematic Literature Review on the Drivers of Impulsive Buying Among Gamers - Annisa Sri Budiman; Abror Abror; Zul Afdal (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
This study aims to analyze the influence of monetization mechanisms in digital games—specifically gacha, loot boxes, and microtransactions—on the impulsive buying behavior of online gamers, taking into account the psychological dynamics involved. The method used is a systematic literature review (SLR) employing a bibliometric approach and following the PRISMA guidelines. Data were obtained from the ScienceDirect and Semantic Scholar databases, with an initial total of 148,869 articles, which were then screened to yield 10 relevant articles for analysis. The findings indicate that probability-based reward mechanisms, immersive gameplay experiences, and psychological factors such as fear of missing out (FOMO), impulsivity, and positive emotions play a significant role in driving impulsive purchases. Additionally, system designs such as probability concealment and selective feedback were found to reinforce cognitive distortions that increase players’ willingness to pay. This study also found that research on this topic is developing in a multidisciplinary manner, linking gamification, digital technology, and consumer behavior. The research’s contribution lies in a comprehensive synthesis of the relationship between gacha mechanisms and digital consumption behavior, while highlighting the importance of self-control in moderating such impulsive tendencies.